1965
DOI: 10.1128/aem.13.5.776-780.1965
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Chlorine Dioxide as a Bactericide1

Abstract: of chlorine dioxide as a bactericide. Appl. Microbiol. 13:776-780. 1965-We found chlorine dioxide to be a more effective disinfectant than chlorine in sewage effluent at pH 8.5. Chlorine dioxide was also found to be a more stable bactericide in relation to pH in the range studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(33 citation statements)
references
References 4 publications
0
32
0
1
Order By: Relevance
“…Nevertheless, knowledge of the action mechanism of ClO 2 is still unexplored. A few studies have been conducted to elucidate the virucidal and bactericidal mechanisms of ClO 2 , and researchers have found that it can damage cell membranes (Berg et al 1986), facilitate protein denaturation (Benarde et al 1965(Benarde et al , 1967Roller and Olivieri 1980;Ogata 2007), and ⁄ or destroy the nucleic acid of micro-organisms (Alvarez and O'Brien 1982;Noss et al 1985;Li et al 2004). Researchers have encountered great difficulty in determining the primary target site as there are so many for ClO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, knowledge of the action mechanism of ClO 2 is still unexplored. A few studies have been conducted to elucidate the virucidal and bactericidal mechanisms of ClO 2 , and researchers have found that it can damage cell membranes (Berg et al 1986), facilitate protein denaturation (Benarde et al 1965(Benarde et al , 1967Roller and Olivieri 1980;Ogata 2007), and ⁄ or destroy the nucleic acid of micro-organisms (Alvarez and O'Brien 1982;Noss et al 1985;Li et al 2004). Researchers have encountered great difficulty in determining the primary target site as there are so many for ClO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…on poultry carcasses (Thiessen et al, 1984). The bactericidal activity of ClO 2 is not affected by high pH or the presence of nitrogenous compounds (Benarde et al, 1965). Since minimal reaction products, including trihalomethanes, are produced in treated water, ClO 2 has been hypothesized to be an effective substitute for aqueous chlorine in treating seafood, red meat, vegetable and stored at Ϫ30ЊC until analyzed for protein or lipid content within 3 days.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorinated compounds constitute another group of chemicals whose potential application as meat sanitizing agents has been studied (Marshall et al, 1977). Chlorine dioxide was found to be an effective bactericide (Benarde et al, 1965) and to be a better antimicrobial agent in turkey processing water than hypochlorite (Baran et al, 1973). In those cases, however, chlorine dioxide was added directly to the aqueous sanitizing solution.…”
Section: Introductionmentioning
confidence: 99%